Design, synthesis, manufacture, characterization and evaluation of lipid nanocapsules in chitosan-iota-carrageenan based hydrogel scaffold as a potential anti-Covid-19 drug delivery system - Mukubwa, Grady Kathondo (Rhodes University, Faculty of Science, Department of Chemistry)
Covid-19 is a deadly viral disease that has been rampant around the world since 2019. Although the successful introduction of the vaccine has reduced the spread of covid-19, new cases and deaths are still being recorded. To date, no specific curative antiviral treatment has been approved for covid-19. However, many existing antiviral drugs have been and are still being studied against covid-19 and some of them, such as Remdesivir, have shown promise and could be repurposed to treat this infection. Unfortunately, antiviral drugs are prone to resistance as most of them have poor biopharmaceutical properties, including low solubility, permeability and bioavailability, which could hinder any clinical success. Recent advances in nanotechnology-based delivery systems have made it possible to improve the biopharmaceutical properties of many drugs, especially those of poorly water-soluble drugs, by formulating them as lipid nanoparticles (LNP). Thus, in order to contribute to the fight against covid-19, this work aimed to develop Lipid Nanocapsules (LNC), based on some natural raw materials, which could improve the biopharmaceutical properties of antiviral drugs. In addition, since covid-19 infection is mainly respiratory, this work also aimed to fabricate a targeted delivery system based on a hydrogel capable of entrapping LNC and ensuring their efficient deposition and release in the lungs. The LNC consisted of a mixture of medium-chain triglycerides oil (MCT oil), crude soy lecithin, tween 80, NaCl and water, while the hydrogel consisted of a chitosan-grafted-iota carrageenan-grafted-poly (acrylamide-co-acrylic acid) system (CS-iCar-p (AAm-Co-AA)). Efavirenz (EFV), a drug with very low water solubility that has recently been demonstrated to have the potential to influence sars-cov-2 life cycle through different targets (3CLP, RdRp, Hellicase, 3'to5'exonuclease, 2'-O-ribose methyltransferase and EndoRNAse), was chosen as the model drug to evaluate the developed delivery system. The combination of LNP and hydrogel results in a delivery system known as the LNP-hydrogel composite, an emerging area of research in the field of drug delivery. To date, no research has reported the design and fabrication of an LNC-CS-iCar-p (AAm-Co-AA) hydrogel composite that could effectively deliver an antiviral drug to the lungs in addition to its advantages in terms of biological activities. Prior to the design of experiment, EFV solubility was assessed in water, labrafac lipophile 1349 and MCT oil. After that, the Design Expert Software version 13 was used to design the different experiments performed in this work. The I-optimal mixture design of experiments was performed for both LNC preparation and CS-iCar-p (AAm-Co-AA) hydrogel synthesis to study the impact of raw materials on the characteristics of these delivery systems. LNC were prepared using the phase inversion method while the free radical precipitation graft copolymerization method was used to synthesize hydrogel. In order to build polynomial models that could predict the amount of drug both LNC and CS-iCar-p (AAm-Co-AA) hydrogel can entrap, a D-optimal (custom) randomized design was performed. Moreover, various characterization techniques were used to investigate the physicochemical properties of the developed delivery systems. Thereafter, drug release studies were performed using a 1% sodium lauryl sulfate solution adjusted to either pH 4 or 7. Solubility studies revealed that EFV was more soluble in labrafac lipophile 1349 and in MCT oil than in water; therefore, given its affordability, MCT oil was used for the LNC formulation. The design of experiment carried out allowed the construction of polynomial models that could predict, on the one hand, the droplet size, the polydispersity index and the Zeta potential of LNC, which were respectively around 50nm, below 0.2 and below -33. On the other hand, the model could predict the swelling capacity of the synthesized hydrogel, which was optimised to about 30,000% (300 g of water to 1 g of hydrogel). This turned out to be influenced by the proportion of polymers, the ratio of monomers as well as the concentration of the cross-linking agent. In addition, the characterization techniques further supported the improvement of EFV solubility by highlighting its conversion into its amorphous state after encapsulation in LNC. They also confirmed successful synthesis of CS-iCar-p (AAm-co-AA) hydrogel. LNC were able to encapsulate about 87% of EFV while the synthesized CS-iCar-p (AAm-co-AA) hydrogel entrapped around 53% of EFV encapsulated in LNC. While LNC were able to release 42% and 27% of EFV after 74 hours in a 1% sodium lauryl sulfate solution (SLS) at pH 7 and pH 4 respectively, the LNC-CS-iCar-p (AAm-co-AA) hydrogel composite released about 50% and 40% of the drug after 9 days in the same release medium. Interestingly, the chemical integrity of the drug was preserved throughout the manufacturing process up to after its release, suggesting that the developed LNC-CS-iCar-p (AAm-co-AA) hydrogel composite could be used as a novel potential anticovid-19 drugs delivery system.
Keywords: Nanocapsules -- Design; Hydrogel; COVID-19 (Disease); Characterization; Drug delivery systems